Treatment strategies of unruptured intracranial aneurysms: A Literature Review - Szema, Agnieszka; Łabuda, Mikołaj; Knychalska, Karolina; Sowińska, Teresa; Bogucka, Adrianna; Sikora, Jakub; Kotkowiak, Agata; Królikowska, Klaudia; Słojewska, Aleksandra; Mentel, Oliwia (Journal of Education, Health and Sport, 2025)
Introduction and purpose Unruptured intracranial aneurysms (UIAs) are often diagnosed incidentally and become a complex clinical dilemma. The main challenge is to choose between invasive treatment and conservative management, considering the low but difficult to predict risk of rupture. The aim of this review is to present current knowledge and approaches regarding UIA management, highlighting both traditional and emerging strategies. Description of state of knowledge Management of UIAs depends on various factors, including aneurysm size, location, morphology, and patient-specific risks. Surgical clipping remains a reasonable method for long-term durability, but more perioperative complications, while endovascular approaches have an advantage due to their less invasive nature, but lower adequate occlusion rate. In selected low-risk patients, conservative monitoring with regular imaging may be appropriate. Advances in computational modeling, artificial intelligence, and hemodynamic analysis are improving our ability to assess rupture risk and tailor treatment plans. However, the lack of universally accepted guidelines continues to complicate decision-making. Conclusion UIA management should be individualized, weighing the risks and benefits of each treatment option. Despite technological progress and improved diagnostic tools, further research and international consensus are needed to establish standardized protocols for clinical practice.